Riba dan bunga bank dalam Islam: analisis hukum dan dampaknya terhadap perekonomian Umat - Kamila, Dina (Maliki Interdisciplinary Journal, 2024)
This article discusses the issue of usury from a legal perspective and its interpretation, as well as bank interest from an Islamic legal perspective. In addition, it also analyzes the impact of usury on the economy from the point of view of Islamic jurists, mufassirin and Muslim economists. There are different opinions regarding the bank interest law and how experts assess its impact on the economy in general at a micro and macro level. Most scholars are of the opinion that bank interest is not permissible (haram). However, several scholars, including Abdullah Yusuf Ali and Muhammad Asad, are of the opinion that compound (unnatural) riba is haram. Non-compound interest is allowed, and this is the type of interest that banks use today. This difference of opinion occurs because the interpreters differ in interpreting these verses.